2007
DOI: 10.1158/1055-9965.epi-07-0634
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 Promoter Polymorphism SNP309 Contributes to Tumor Susceptibility: Evidence from 21 Case-Control Studies

Abstract: Since the identification of a well-characterized functional polymorphism named SNP309 in MDM2, abundant studies were published in the last 2 years to evaluate the association between SNP309 and tumor risk in diverse populations. However, the results remain conflicting rather than conclusive. Because a single study may have been underpowered to detect the effect of low-penetrance genes, a quantitative synthesis to accumulate data from different studies may provide better evidence on the association of genetic v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

11
102
4
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(118 citation statements)
references
References 47 publications
11
102
4
1
Order By: Relevance
“…7 On the other hand, our finding of a weak negative association of the MDM2 G allele is in contrast with reports of its preferential transmission to RB patients, 13 modifier role in Li-Fraumeni syndrome 9,19 and association with common cancers. 20 Nevertheless, our findings seem plausible, considering that the association only holds in p53-mutated cancers. 20 If confirmed in other independent studies, the pattern we report here of positive association of p53 Pro/Pro and negative association of MDM2 GG would depict a new scenario with different functional and therapeutic implications.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…7 On the other hand, our finding of a weak negative association of the MDM2 G allele is in contrast with reports of its preferential transmission to RB patients, 13 modifier role in Li-Fraumeni syndrome 9,19 and association with common cancers. 20 Nevertheless, our findings seem plausible, considering that the association only holds in p53-mutated cancers. 20 If confirmed in other independent studies, the pattern we report here of positive association of p53 Pro/Pro and negative association of MDM2 GG would depict a new scenario with different functional and therapeutic implications.…”
mentioning
confidence: 63%
“…20 Nevertheless, our findings seem plausible, considering that the association only holds in p53-mutated cancers. 20 If confirmed in other independent studies, the pattern we report here of positive association of p53 Pro/Pro and negative association of MDM2 GG would depict a new scenario with different functional and therapeutic implications. …”
mentioning
confidence: 63%
“…[9][10][11][12] A polymorphism replacing arginine (R72) with proline (P72) at position 72 in p53 (codon72 polymorphism, referred to as R72P) has been reported to affect p53 function. 13 It has been shown that R72 increases the affinity of p53 to MDM2, affects its export from the nucleus, and provides increased apoptotic potential.…”
mentioning
confidence: 99%
“…The variant allele has been shown to have increased affinity to the MDM2 transcriptional activator Sp1, resulting in higher levels of MDM2 protein and subsequent attenuation of the p53 pathway. This polymorphism is associated with accelerated tumour formation in both hereditary and sporadic cancers (for a review see Bond and Levine, 2007) and a meta-analysis recently concluded that variant homozygote G/G was associated with a significantly increased risk of all types of tumours (Hu et al, 2007). Its possible effect on anticancer drug response remains to be established, but a recent study comparing cell lines with different MDM2 genotypes revealed a lower sensitivity of the G/G homozygous variant to topoisomerase II-interfering drugs (Nayak et al, 2007).…”
mentioning
confidence: 99%